Postharvest handling intervention for banana var la tundan grown in marginal upland areas in Inopacan, Leyte - Quevedo, Marcelo A.; Ramos, Arsenio D.; Sta. lglesia, Ness Marie; Notarte, Kris Benzon V. (Annals of Tropical Research, 2017)
The study was conducted to evaluate the effectiveness of packaging materials for transport and simple storage techniques of banana fruits planted by the upland farmers of lnopacan, Leyte and to identify and introduce the suitable postharvest intervention for their adoption. The use of plastic crates and rattan basket significantly minimized bruises and scratches of banana fruits during transport compared to plastic sack. Providing lining materials further reduced these injuries during transport. As a result of minimal damage during transport, the shelf life was extended during storage at ambient condition. On the other hand, harvested banana fruits were not stored as these were directly sold to the market during market days (tabo) or directly bought by middle men from the farm. However, in some instances where there is a difficulty in transport due to impassable roads, farmers are obliged to keep the harvested banana for sometime in their homes or collection center. Banana var. ‘Latundan’ fruits in hands or in bunch stored using MAP (PE bags) with diffusion holes had better postharvest performance, particularly lesser weight reduction, extended ripening (based on peel color changes & firmness), lower incidence and degree of decay and acceptable sensory quality ratings. In contrast, fruits in MAP without diffusion hole had inferior postharvest behavior.